Consumption smoothing across seven countries: A time series analysis - Bernd Fitzenberger (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
With representative agents maximizing their expected Xife time Utility, it can be shown under certain functional form assumptions that consumption follows a random walk and should be cointegrated across countries, because in an optimal risk pooling arrangement agents smooth consumptions with respect to erratic income movements. These implications are analyzed for the G-7-countries using spectral based and coIntegration techniques. Also the contemporaneous and causal feedback and a factor analytical model are estimated for the first differences of the consumption series. The results indicate little comovement of consumption across countries for annual data from 1950 to 1985.
Keywords: 330